Alicia en el país de las maravillas ; A través del espejo - Carroll, Lewis, 1832-1898 (Akal bolsillo, 2012)
By falling down a rabbit hole and stepping through a mirror, Alice experiences unusual adventures with a variety of nonsensical characters.